Constituting neoliberal subjects? 'Aspiration' as technology of government in UK policy discourse - Spohrer, Konstanze; Stahl, Garth; Bowers-Brown, Tamsin (Journal of education policy, 2018)
Since the 2000s, successive governments in the United Kingdom and elsewhere have embraced the idea of 'raising aspiration' among young people as a solution to persisting educational and socio-economic inequalities. Previous analyses have argued that these policies tend to individualise structural disadvantage and promote a 'deficit' view of working-class youth. This paper adopts a novel approach to analysing aspiration discourses combining Michel Foucault's four dimensions of 'ethics' and Mitchell Dean's notion of 'formation of identities'. Applying Foucault's and Dean's work in this way provides a new lens that enables an examination of how policy encourages particular forms of subjectivation, and, therefore, seeks to govern individuals. The findings presented in the paper complicate previous research by showing that raising aspiration strategies portray disadvantaged youth both in terms of 'deficit' and 'potential', resulting in a requirement for inner transformation and mobility through attitudinal change. The paper concludes with a discussion of the implications for the identity formation of young people and for conceptualising contemporary forms of governmentality.